Transcriptome data reveal Syndermatan relationships and suggest the evolution of endoparasitism in Acanthocephala via an epizoic stage. - Alexandra R Wey-Fabrizius (Public Library of Science (PLoS), 2014)
The taxon Syndermata comprises the biologically interesting wheel animals ("Rotifera": Bdelloidea + Monogononta + Seisonidea) and thorny-headed worms (Acanthocephala), and is central for testing superordinate phylogenetic hypotheses (Platyzoa, Gnathifera) in the metazoan tree of life. Recent analyses of syndermatan phylogeny suggested paraphyly of Eurotatoria (free-living bdelloids and monogononts) with respect to endoparasitic acanthocephalans. Data of epizoic seisonids, however, were absent, which may have affected the branching order within the syndermatan clade. Moreover, the position of Seisonidea within Syndermata should help in understanding the evolution of acanthocephalan endoparasitism. Here, we report the first phylogenomic analysis that includes all four higher-ranked groups of Syndermata. The analyzed data sets comprise new transcriptome data for Seison spec. (Seisonidea), Brachionus manjavacas (Monogononta), Adineta vaga (Bdelloidea), and Paratenuisentis ambiguus (Acanthocephala). Maximum likelihood and Bayesian trees for a total of 19 metazoan species were reconstructed from up to 410 functionally diverse proteins. The results unanimously place Monogononta basally within Syndermata, and Bdelloidea appear as the sister group to a clade comprising epizoic Seisonidea and endoparasitic Acanthocephala. Our results support monophyly of Syndermata, Hemirotifera (Bdelloidea + Seisonidea + Acanthocephala), and Pararotatoria (Seisonidea + Acanthocephala), rejecting monophyly of traditional Rotifera and Eurotatoria. This serves as an indication that early acanthocephalans lived epizoically or as ectoparasites on arthropods, before their complex lifecycle with arthropod intermediate and vertebrate definite hosts evolved.